Nanopore sequencing enables combined detection of USP7 variants and a known Hao-Fountain syndrome episignature - van der Laan, Liselot; Haagmans, Martin A.; Venema, Andrea; Kerkhof, Jennifer; Levy, Michael A.; Briuglia, Silvana; Caro, Pilar; Sailer, Sebastian; Schaaf, Christian P.; Sadikovic, Bekim; van Haelst, Mieke M.; van Gijn, Mariëlle; et al. (Frontiers in Genetics, 2026)
BackgroundHao-Fountain syndrome (HAFOUS) is a rare neurodevelopmental disorder caused by pathogenic variants in the USP7 gene. This condition is associated with a distinct DNA methylation episignature that aids its diagnosis. While microarray-based methods have traditionally been used to detect these DNA methylation signatures, long-read nanopore sequencing offers the potential for simultaneous genetic and epigenetic analysis.MethodsWe analyzed DNA extracted from the blood of five individuals carrying pathogenic USP7 variants or deletions using Oxford Nanopore direct long-read sequencing. This approach enabled the detection of both genetic variants and native 5 mC methylation profiles. Methylation patterns were analyzed at known HAFOUS-specific episignature probes and compared against control samples using UMAP and hierarchical clustering. Classification was further validated using the EpiSign™ platform.ResultsNanopore sequencing successfully identified all pathogenic USP7 variants, including SNVs and structural deletions. DNA methylation analysis demonstrated clear separation between HAFOUS patients and controls, consistent across both nanopore and EPIC array platforms. All cases were correctly classified using the EpiSign™ pipeline, confirming the presence of the HAFOUS episignature.ConclusionThis study demonstrates that nanopore sequencing enables accurate, simultaneous detection of USP7 variants and the associated HAFOUS methylation episignature. These findings support the clinical utility of long-read sequencing as an integrated diagnostic tool for neurodevelopmental disorders, offering a unified platform for comprehensive genomic and epigenomic profiling.